Clinical significance of serum hepcidin in the diagnosis and treatment of patients with anemia of chronic disease: a meta-analysis. (19th May 2021) - Han, Jie; Wang, Kai
Abstract: Objective: To systematically evaluate the value of serum hepcidin in the diagnosis of Anaemia of Chronic Disease (ACD) in order to provide appropriate treatment. Methods: Literature search was performed in PubMed, EMbase, Cochrane Library, CNKI, CBMdisc and CSPD till Jan, 2020. Studies using hepcidin assay for the diagnosis of ACD were included. Two researchers selected the literature according to the pre-defined inclusion and exclusion criteria. Meta-analysis was performed using Stata 15.0. Results: A total of 10 studies were included, including 739 patients with 402 ACD patients. Heterogeneity test results suggest that there is no statistical heterogeneity between the included studies and Meta- analysis was performed using a fixed-effects model. Results showed that serum hepcidin levels in patients with ACD combined with SEN, SPE, PLR, NLR, and Diagnostic OR were 0.94 [95% CI (0.90, 0.96)], 0.85 [95% CI (0.81, 0.88)], 6.1 [95% CI (4.8, 7.6)], 0.08 [95% CI (0.05, 0.12)] and 81 [95% CI (47, 139)] respectively. The area under the SROC curve (AUC) value was 0.91. Conclusion: Serum hepcidin assay is a valuable method to diagnose ACD in patients. However, due to the limitations of the quantity and quality of the research, the above conclusions need more research to verify.